Revision of Undergraduate Engineering Curriculum with Emphasis on Project-Based Teaching Learning Approach - Case Study of KTU - Suryan, Abhilash; Radhakrishnan, V.; Ramachandran, G.; Abdul Rahman, M.; Isaac, Kuncheria P. (Journal of Engineering Education Transformations, 2021)
APJ Abdul Kalam Technological University in Kerala was founded in the year 2014. The University has introduced many path breaking initiatives for modernizing and upgrading technical education in Kerala. Extensive consultations were held for the preparation of the new curriculum for the University with various stake holders including eminent academicians, distinguished industrialists, faculty members from affiliated institutions and representatives of students. A detailed survey of the existing curriculum in all the universities in Kerala was conducted prior to the preparation of the curriculum for the Technological University. This paper presents certain novel features introduced by the University in the curriculum for the under graduate programmes in engineering.